Endogenous Development in The Optimization Minapolitan Program in Kalanganyar Village, Sidoarjo Regency (Future Science, 2021)
In 2010, the Ministry of Marine Affairs and Fisheries released a policy of accelerated development of the area based on the potential of marine and fisheries, or Minapolitan. Minapolitan is implemented in several regions in Indonesia, one of which is in the Village of Kalanganyar, Sidoarjo Regency. Kalanganyar is known as a producer of premium milkfish and shrimp, processed milkfish, as well as being the location of the most prominent fishing tours in Sidoarjo. This potential causes Kalanganyar to be called “the village of the fish”. Hence, this study aims to identify the endogenous development factors in the implementation of Minapolitan in Kalanganyar. This study uses a qualitative approach with the following data collection techniques: interviews, observation, document collection, and focus group discussion. Specifically, data analysis techniques using an interactive model consist of the stages of reduction, display, and conclusion. As for the test of the data validity, the writer utilized tools for trust checking, transferability, dependence, and certainty basis. The results showed that in general, the factors of entrepreneurship are quite fulfilled. However, there are some aspects to be considered; such as the provision of seedlings banding, an increase in capital for small businesses, the modernization of production equipment for processed milkfish, assistance for market expansion, and the construction of a hub for souvenirs and gift shops. Nevertheless, the leadership factor has been fulfilled. Formal and informal leaders have given good support in the optimization of Minapolitan. As for the third factor, the institution has also been well construed. It can be seen from the formation of village-owned enterprises, which are expected to become an economic catalyst, as well as the presence of rules in the implementation of the business. Thus, it can be concluded that in general, the factors of endogenous development in the implementation of minapolitan di Kalanganyar village have been well accomplished.